Optimizing nonstationary 38-GHz pulse-train relativistic backward wave oscillator with low guiding magnetic field; Technical Physics Letters; Vol. 34, № 9 - Ermakov A. E.; Zhakov S. V.; Mesyats G. A. Gennady Andreyevich; Rostov V. V.; Ul'maskulov M. R.; Sharypov K. A.; Shpak V. G.; Shunailov S. A.; Yalandin M. I. (2008, 2008)
В фонде НТБ ТПУ отсутствует